Justice in the Balance: State vs. Civil Society Perspectives on the Climate Change Regime - Manzo, Rosa (Christ University Law Journal, 2024)
Justice cuts across climate change in various ways. There are two viewpoints from which one can evaluate the degree of justice. The first comes from the perspective of a civil society, the other from a state’s point of view. The final conclusion is that the degree of justice varies in accordance with the viewpoints, which on their part depend on where the evaluation is carried out. While a state’s perspective on the justice of a climate regime is based on the ratio of benefits against costs derived from international climate agreements, a civil society’s perspective is based on the evaluation of how the agreement can provide an effective response to adverse effects. As has been shown, States’ views differ from those of the civil society. This means that what is just to States can differ significantly from what civil society considers to be just. As a consequence, an answer to justice and its role in designing the international climate regime should start taking into consideration the perspective from which the issue is viewed. By highlighting the diverging priorities—state-centric cost-benefit analyses versus civil society’s focus on tangible outcomes for communities—the paper aims to show that justice is a context-dependent concept within climate governance.